Pediatric Inflammatory Multisystem Syndrome With Central Nervous System Involvement and Hypocomplementemia Following SARS-COV-2 Infection. Issue 8 (August 2020) - Regev, Tslil; Antebi, Maayan; Eytan, Danny; Shachor-Meyouhas, Yael; Ilivitzki, Anat; Aviel, Yonatan Butbul; Ben-Ari, Josef
Abstract : Pediatric inflammatory multisystem syndromes associated with Severe Acute Respiratory Syndrome Coronavirus 2 are emerging in recent reports. We describe a patient with critical illness consistent with atypical Kawasaki disease with cardiac dysfunction and abdominal involvement presenting weeks after Severe Acute Respiratory Syndrome Coronavirus 2 infection. Our patient showed unique central nervous system involvement with small vessel vasculitis and profound hypocomplementemia, both not previously reported in case descriptions and may hint at possible disease mechanisms.